A longitudinal study of the effect of Antarctic residence on energy dynamics and aerobic fitness - Alistair Simpson; Veronica Maynard (International Journal of Circumpolar Health, 2012)
Objectives: To investigate the effect of Antarctic residence on energy dynamics and aerobic fitness over the course of a year in over-wintering personnel. Study design: A prospective longitudinal observational study. Methods: A convenience sample of personnel over-wintering at Rothera Research Station in Antarctica was studied. Body weight, body fat, food intake, activity and aerobic fitness were recorded every 30 days for 1 year. Body weight, body fat and food intake were measured using weighing scales, skinfold callipers and diet records, respectively; activity was measured using accelerometer-based activity trackers and aerobic fitness using a treadmill protocol. Climate markers of temperature and sunlight hours were also recorded. Results: Twenty-one subjects took part in the study over the 12-month period. A statistically significant increase in body weight and body fat in winter was observed (p=0.012 and p=0.049, respectively). There were no statistically significant trends in activity, food intake or aerobic fitness. Conclusions: There were significant seasonal changes in body weight and body fat, with both measures increasing in winter but no significant changes in the other main outcome measures.